2009
DOI: 10.1039/b901075k
|View full text |Cite
|
Sign up to set email alerts
|

MEH-PPV by microwave assisted ring-opening metathesis polymerisation

Abstract: Excellent control in the synthesis of MEH-PPV can be achieved by microwave assisted, ring-opening metathesis polymerisation (ROMP) of [2.2]paracyclophanedienes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…This 5:5 ratio implies the same environment for each double bond (cis and trans) with a location of one methoxy and one 2-ethylhexyloxy substituent in proximity to each double bond. 34 Therefore, a coordination of the methoxy substituent to ruthenium during the polymerization process can be concluded.…”
Section: Resultsmentioning
confidence: 99%
“…This 5:5 ratio implies the same environment for each double bond (cis and trans) with a location of one methoxy and one 2-ethylhexyloxy substituent in proximity to each double bond. 34 Therefore, a coordination of the methoxy substituent to ruthenium during the polymerization process can be concluded.…”
Section: Resultsmentioning
confidence: 99%
“…A direct route to soluble PPVs via ROMP of alkoxy or alkyl substituted paracyclophanedienes in the presence of the second generation Grubbs’ initiator has been reported by Yu and Turner . They demonstrated that the resulting PPVs exhibited predictable and well‐controlled molecular weights with low PDI by varying the monomer to initiator ratio, thereby confirming the living nature of the polymerization.…”
Section: Introductionmentioning
confidence: 78%
“…[30] MEH-PPV displays am ax absorption peak at l max = 510 nm, as well as an emission around 550 nm, with aprominent shoulder at 600 nm. [30] MEH-PPV displays am ax absorption peak at l max = 510 nm, as well as an emission around 550 nm, with aprominent shoulder at 600 nm.…”
Section: Angewandte Chemiementioning
confidence: 99%